Balanced nutrition education as an effort to prevent nutritional problems in toddlers within the SEHATI PT Pertamina program - Saswini, Andi Ade Ula; Haris, Muhammad; Jarwanto, Dwi (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
Nutritional problems among toddlers remain a significant public health issue, often caused by limited knowledge of balanced nutrition. This community service activity aimed to address this issue by improving the knowledge of mothers with toddlers regarding balanced nutrition as an effort to prevent nutritional problems. The beneficiaries were 21 mothers participating in the SEHATI Pertamina program within the Tabaringan Community Health Center (Puskesmas Tabaringan) working area, Makassar. The program included educational counseling and practical training on making anchovy sausages as a nutritious food alternative. The methods used were lectures and interactive discussions, followed by knowledge assessments through pre-tests and post-tests. Factors contributing to the lack of knowledge about balanced nutrition included maternal factors, household environment, poor food quality, inappropriate feeding practices, food and beverage safety, breastfeeding, infections, socio-economic and political conditions, healthcare services, education, social and cultural aspects, agricultural and food systems, water, sanitation, and the environment. The evaluation results showed a significant improvement in the participants' knowledge. Before the education, 28% of participants had good knowledge, which increased to 61% after the program, indicating the effectiveness of educational interventions in enhancing the understanding of balanced nutrition. The findings highlight the importance of continuous educational interventions to improve maternal knowledge and practices related to child nutrition, which can contribute to reducing nutritional problems in the long term.